CURRENT STRATEGIES IN THE PREVENTION OF POSTOPERATIVE INFECTIONS IN SPINAL SURGERY - REHMAM , KU; ALI , A; SATTAR , A; KHAN , SK; KHAN , MZ (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to analyze the strategies used to prevent postoperative infections in spinal surgery and evaluate their effectiveness in reducing the frequency of infections. The study design was retrospective and was conducted between January and December 2021 at the Department of Orthopedic & Spine Surgery, Hayatabad Medical Complex. The study included a total of 90 patients who were divided into two groups based on the preventative techniques used. Group A (n=45) received standard preventive measures, such as preoperative antibiotics, accurate aseptic techniques, and postoperative wound care. In comparison, Group B (n=45) was given supplementary preventive measures such as antibiotic-impregnated bone grafts and wound irrigation with antiseptic solutions. The occurrence of postoperative infections, namely surgical site infections (SSIs) and deep wound infections, was documented and compared between the two groups. The mean age of patients in Group A was 55.2±8.6 years, while it was 57.8±9.2 years in Group B. Group A consisted of 27 (60%) male and 18 (40%) female patients, whereas Group B had 29 (64.44%) male and 16 (35.55%) female patients. Nine (20%) patients in Group A developed postoperative infections, while only three (6.7%) in Group B developed infections. The difference in postoperative infection incidence between the two groups was statistically significant (p<0.05). Similarly, the incidence of SSIs was lower in Group B (4.4%) than in Group A (15.6%) (p<0.05). Most patients in both groups (55.55% in Group A and 48.88% in Group B) received lumbar fusion surgery. Cervical fusion surgery was performed on 10 (22.22%) Group A patients and 12 (26.66%) Group B patients. Decompression surgery was performed on eight (17.77%) patients in Group A and nine (20%) individuals in Group B. The study’s findings indicate that preventive techniques, such as antibiotic-impregnated bone grafts and wound irrigation with antiseptic solutions, can significantly reduce postoperative infections in spine surgery. However, further research is needed to determine the long-term effectiveness of these prevention approaches and explore alternative methods for preventing postoperative infections in spine surgery.